Criminal Law: Machinery for the Protection of Environment - Juyal Anthwal, Sushma; Bahuguna, Rajesh (International Journal of Psychosocial Rehabilitation, 2020)
Criminal Law has consistently been considered as the most proper medium to settle different social, financial and political issues. With the development and the improvement of society, it was seen that there was a continuous move in the law mediating procedure and criminal law was viewed as the most advantageous answer for serious issues. This was the explanation behind figuring one all-inclusive code for all infringement of laws and the violators to be punished with imprisonment and fine. In the previous decades, with urbanization and industrialization, a compelling impulse for the assurance and preservation of condition has additionally equipped around the world. Indian rules provided for the security of condition and the Lex loci, for example, The Indian Constitution has made it both a basic right as well as an essential obligation to secure and move in the direction of the preservation of the earth. The problem with Indian enactments lie in the way that these enactments have recently given the components for protection yet needed with respect to successful execution and implementation of the same. However, the inquiry has likewise happened with regards to the connection between criminal law and environmental protection. There have been endless discussions on the connection between criminal law and environmental law, the viability of criminal enactments in ensuring and advancing environmental law and the advantages and disadvantages of environmental protection measures. Along with these lines, more or less, it tends to be expressed in spite of the tremendous efforts by the different state lawmaking bodies and national legislation, environment is being exhausted, and it hassled to widespread destruction and devastation which should be controlled. The paper basically aims to point out the possible causes for environmental degradation and the criminal remedies to curb such degradation with special emphasis on the role of criminal law in protection of environment and the interrelationship between environment and criminal law.